ANALISIS INTEGRASI PASAR MODAL INDONESIA DENGAN PASAR MODAL ASEAN PERIODE 2021-2023 - Dwi, Dwi Nur Aeni; Stefhani, Yosi (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
This study aims to determine whether there is a correlation between the Indonesian stock market and the stock markets ASEAN member countries. Namely Malaysia, the Philippines, Singapore, Thailand, and Vietnam, during the period 2021-2023. The population used in this study includes the ASEAN Stock Exchange Indices are: the Kuala Lumpur Stock Exchange (KLSE) Index, the Philippine Stock Exchange Index (PSE), the Straits Times Index (STI), the Stock Exchange of Thailand (SET), and the Vietnam Ho Chi Minh Stock Index (VNI). The data analysis method used is the Bivariate Pearson Correlation. The results of the study fund shows that there is a correlation between the Indonesian stock market and the markets of Malaysia and Singapore. However, there is no correlation with the stock markets of the Philippines, Thailand, and Vietnam.